Packaging method for improving reliability of green fluorescent powder
By adopting a multi-layer structural design of dynamic self-healing underlying packaging, molecular sieve composite barrier layer and rigid molecular chain barrier layer in phosphor packaging, the service life and stability of the phosphor packaging layer in high temperature and high humidity environments is solved, and the packaging effect with high mechanical strength, low water and oxygen transmittance and good optical performance is achieved.
Patent Information
- Application Number
- CN202510020385.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the service life and stability of the phosphor packaging layer in high temperature and high humidity environments are insufficient, and the thermal expansion coefficient matching of the multi-layer packaging structure is poor and the interface bonding force is insufficient, resulting in interlayer crack propagation and limited packaging optical performance.
Dynamic self-healing underlying packaging is adopted, including dynamic chemical network epoxy resin matrix, dynamic bond inlet agent, nanofiller and surfactant, to form a package layer with high mechanical strength and chemical stability. Then the molecular sieve composite barrier layer and the rigid molecular chain barrier layer are coated on the dynamic self-healing base layer. Through multi-layer structure design and optimization process, the water-oxygen barrier performance and mechanical strength of the package are improved.
It significantly improves the crack healing ability, mechanical stability and water-oxygen barrier properties of the encapsulation layer, extends the service life of the encapsulation layer, and maintains optical transparency and light-color stability in high temperature and high humidity environments.
Smart Images

Figure CN119894194A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optoelectronic device packaging, and in particular to a packaging method for improving the reliability of cyan phosphor powder. Background Art
[0002] LED chip packaging technology in the optoelectronic field has been widely used in recent years, among which phosphor packaging is the key link to achieve high light efficiency and multi-color temperature light sources. Phosphors absorb blue light or ultraviolet light emitted by the chip and convert it into a wide spectrum of visible light, thereby achieving white light output with high color rendering. In order to ensure the luminous efficiency and stability of the phosphor, the packaging material not only needs to have good light transmittance, but also needs to provide reliable mechanical protection and long-term barrier capabilities. In the prior art, epoxy resins, polyimides and silicone materials are widely used as packaging matrices due to their excellent optical and thermal properties. However, as the power density of LED chips increases, the phosphor packaging layer is exposed to high temperature and high humidity environments for a long time, and its service life and stability still face severe challenges.
[0003] In order to cope with the harsh use environment, multi-layer packaging has gradually become the mainstream direction of phosphor packaging. Common multi-layer packaging includes flexible substrate layer, inorganic barrier layer and other designs. The flexible layer provides stress buffering, and the inorganic layer enhances the barrier performance. Although these technologies have alleviated the impact of water and oxygen intrusion on phosphors to a certain extent, due to the poor matching of thermal expansion coefficients of materials between layers, insufficient interface bonding strength, and problems of interlayer crack propagation, the multi-layer packaging structure is still difficult to meet the long-term reliability requirements of high-performance LED chips. In addition, the barrier performance of existing materials mostly relies on high density and high thickness design, which cannot effectively balance the contradiction between film transparency and barrier ability, limiting the optical performance of the package. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a packaging method for improving the reliability of cyan phosphors, solving the problems of poor thermal expansion coefficient matching, insufficient interface bonding, and interlayer crack expansion and limited packaging optical performance in the prior art.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A packaging method for improving the reliability of cyan phosphors comprises the following steps: S1. forming a dynamic self-repairing bottom package on the surface of the chip, wherein the dynamic self-repairing bottom package comprises a dynamic chemical network epoxy resin matrix, a dynamic bond introducing agent, a nanofiller and a surfactant; Dynamic chemical network epoxy resin matrix (60-80wt%): Epoxy resin with dynamic covalent bonds (disulfide bonds, imine bonds) is selected. This type of matrix material has reversible chemical bond function and can achieve self-repair under environmental stimulation (increased temperature). At the same time, it has a high cross-linking density and can provide excellent mechanical strength and chemical stability.
[0006] Dynamic bond introducing agent (5-15 wt%): by introducing disulfide groups, a dynamic covalent bond network is formed, which can break and reorganize when damaged, further enhancing the crack healing ability.
[0007] Nanofiller (3-10 wt%): Multi-walled carbon nanotubes (MWCNT) are used to enhance the thermal conductivity of the matrix on the one hand, and to reduce the molecular gap through the synergistic effect of the filler and the matrix on the other hand, effectively reducing the water and oxygen permeability.
[0008] Surfactant (0.5-2 wt%): Silane coupling agent (γ-aminopropyltriethoxysilane) is used to enhance the interfacial bonding force between the filler and the epoxy matrix, ensure the uniform dispersion of the filler, and avoid microscopic defects.
[0009] Preparation process: The epoxy resin matrix and the dynamic bond introducing agent are mixed in proportion, with a stirring speed of 2000-3000 rpm for 30-60 minutes; multi-walled carbon nanotubes and surfactants are added, and vacuum degassing (vacuum degree -0.08 to 0.1 MPa for 15-30 minutes) is performed after high-speed stirring; The mixture is evenly coated on the surface of the chip, and the coating thickness is controlled to be 20 to 50 μm; The initial curing is carried out at 80-100°C for 30-60 minutes, and then cured at 150-170°C for 1-2 hours.
[0010] S2. coating a molecular sieve composite barrier layer on the dynamic self-repairing bottom package, wherein the molecular sieve composite barrier layer comprises a polydimethylsiloxane matrix, a molecular sieve filler, an inorganic filler and a toughening agent; Polydimethylsiloxane (PDMS) substrate (70-90 wt%): provides a flexible structure to buffer the thermal expansion of the bottom layer, while its low surface energy and excellent hydrophobic properties further enhance the barrier ability to water and oxygen.
[0011] Molecular sieve filler (5-15wt%): ZSM-5 molecular sieve or metal organic framework (MOFs, MIL-101) is used, whose microporous structure selectively blocks water and oxygen molecules and prolongs the diffusion path through the molecular sieve effect.
[0012] Inorganic filler (5-10 wt%): Nano-montmorillonite is introduced. This flake filler is oriented and distributed in the matrix to form a laminated barrier, further preventing water and oxygen penetration.
[0013] Toughening agent (3-8 wt%): enhances the toughness and mechanical stability of the material and prevents interlayer detachment due to external stress.
[0014] Preparation process: The polydimethylsiloxane matrix and the molecular sieve filler are mixed in proportion and then ultrasonically dispersed (frequency 40-60 kHz, time 30-60 minutes); Add nano-montmorillonite and toughening agent, stir at high speed and then vacuum degassing (vacuum degree -0.08 to -0.1 MPa, time 10 to 20 minutes); The coating is carried out by spin coating process, with a spin coating speed of 2000-3000 rpm to form a uniform thin film layer with a thickness controlled at 10-30 μm; and the coating is cured at 80-100° C. for 8-12 hours.
[0015] S3, spraying a rigid molecular chain barrier layer on the molecular sieve composite barrier layer, wherein the rigid molecular chain barrier layer comprises a polyimide matrix, an inorganic filler and a cross-linking agent; Polyimide (PI) matrix (60-80 wt%): provides high heat resistance, high mechanical strength and chemical stability, and further enhances the protection performance of the encapsulation layer.
[0016] Inorganic filler (10-20 wt%): The introduction of fluorinated quartz particles improves the mechanical strength and water and oxygen barrier capability of the rigid layer.
[0017] Cross-linking agent (1-5 wt%): a trifunctional cross-linking agent (trimethylolpropane triacrylate) is used to increase the cross-linking density of the material and enhance the structural stability.
[0018] Preparation process: After the polyimide matrix, inorganic filler and cross-linking agent are mixed, high-speed stirring (speed 1000-1500 rpm, time 10-30 minutes) is adopted; The coating is carried out by spraying process, the spraying pressure is controlled at 0.1-0.2MPa, the spraying distance is 10-20cm, and a film with a thickness of 10-15μm is formed; Curing at 200-250°C for 20-40 minutes.
[0019] S4, curing each layer in turn, and performing heat treatment on the entire package after completion; Interface bonding strengthening: Heat treatment promotes the chemical reaction of silane coupling agent at the interface between layers and improves the interlayer bonding strength.
[0020] Thermal stress relief: Thermal treatment eliminates residual stress generated during the curing process, avoiding the risk of cracking or delamination of the encapsulation layer during subsequent use.
[0021] Preferably, the dynamic chemical network epoxy resin matrix is bisphenol A epoxy resin or epoxy resin containing imide bonds, accounting for 60-80% by mass; The core of the dynamic chemical network is to enable the packaging material to have crack healing ability through the introduction of reversible chemical bonds (imine bonds or disulfide bonds). When the material produces microcracks due to thermal stress or mechanical damage during operation, the dynamic bonds can break to absorb external stress, and then rebond at a higher temperature (the ambient temperature when the chip is working) to repair the cracks, thereby extending the service life of the packaging layer. This dynamic repair process is based on the principles of chemical thermodynamics and kinetic equilibrium, and can be repeated many times under certain conditions to achieve self-healing of cracks.
[0022] Disulfide bond repair: Disulfide bonds can be cleaved at high temperatures to form sulfur free radicals. When the cracks are closed, the sulfur free radicals recombine to form a complete chemical network.
[0023] Imine bond repair: Imine bonds can undergo reversible cleavage (decomposition into amines and aldehydes) at a certain temperature. When the cracks heal, the amines and aldehydes recombine to form imine bonds.
[0024] Reinforcement mechanism of high cross-linking density: Bisphenol A epoxy resin significantly improves the mechanical strength and chemical stability of the material by forming a three-dimensional network structure with high cross-linking density. This high cross-linking density reduces the mobility of molecular segments, reduces the diffusion rate of water and oxygen molecules, and improves the aging resistance of the material in high temperature and high humidity environments.
[0025] Nanofiller barrier and thermal conductivity: Multi-walled carbon nanotubes can form a microscopic filling structure in the matrix due to their extremely high aspect ratio and excellent thermal conductivity. On the one hand, these fillers can effectively compress the molecular gaps of the matrix and increase the resistance to water and oxygen diffusion; on the other hand, carbon nanotubes provide excellent thermal conductivity, quickly conducting the heat of the chip when it is working to the outside of the packaging layer, thereby reducing the risk of thermal failure of the phosphor.
[0026] Interface enhancement: The introduction of surfactant (silane coupling agent) combines with the surface of inorganic filler through chemical bonds, enhancing the compatibility of inorganic filler with epoxy resin matrix. The interfacial bonding force formed by the coupling agent avoids microscopic defects and interface delamination caused by uneven distribution of filler, thereby significantly improving the overall stability of the encapsulation layer.
[0027] Overall synergy: The self-healing effect of dynamic chemical bonds, the structural stability provided by high cross-linking density, the barrier and thermal conductivity of nanofillers, and interface enhancement measures work together to form a packaging bottom structure that has both dynamic response capabilities and high mechanical strength and low permeability. This structure can effectively prevent the intrusion of external water and oxygen, and at the same time extend the service life through dynamic repair when the packaging layer is damaged.
[0028] Preferably, the dynamic bond introducing agent is a disulfide group precursor, accounting for 5 to 15% by weight; Disulfide group precursors: Preferably, 2,2'-disulfide dibenzoic acid or disulfide diacrylate is used. Such compounds provide a chemical basis for crack repair through the thermosensitive and reversible chemical reaction of disulfide bonds, which form or break under dynamic conditions.
[0029] Matrix Compatibility: The disulfide group precursor reacts with the epoxy resin matrix (bisphenol A type epoxy resin) through its thiol or carboxyl functional group, is evenly dispersed in the matrix, and forms a stable bond with the matrix chemical network, avoiding the phase separation problem caused by poor compatibility.
[0030] Ratio and range: The mass proportion of the dynamic bond introducing agent is 5-15%. If it is less than 5%, sufficient dynamic bond density cannot be formed and crack healing function cannot be achieved; if it is higher than 15%, the matrix strength decreases or the cross-linking density is insufficient due to excessive dynamic bonds.
[0031] Dynamic response mechanism of disulfide bonds: The core property of the disulfide group is its dynamic bonding ability. The SS bond has a relatively low bond energy (~60 kcal / mol) and can undergo reversible cleavage reactions under thermal or mechanical stress: RSSR←RS · +SR · When a crack appears, the disulfide bond breaks to generate sulfur free radicals. After the crack closes, the free radicals recombine to form disulfide bonds, completing the self-repair process.
[0032] Chemical balance during crack healing: Crack healing is a chemical process controlled by thermodynamics and kinetics. Under thermal stimulation (high temperature conditions in the chip working environment), the cleavage reaction and the rebonding reaction reach a balance, ensuring that the dynamic chemical network can repair microcracks and prevent crack propagation.
[0033] Effect of dynamic bond density on material properties: Density optimization: Introduce 5-15% disulfide group precursors to form an appropriate amount of dynamic bonds. A lower dynamic bond density cannot effectively cover the crack distribution area, resulting in insufficient repair performance; while an excessively high dynamic bond density will reduce the cross-linking density of the matrix, thereby weakening the mechanical properties of the material.
[0034] Self-repairing ability: The dynamic bond can be broken and recombined multiple times at high temperatures, giving the material long-term repair capabilities and extending the packaging life.
[0035] Synergistic effect of disulfide bonds and matrix cross-linking: The disulfide bonds are embedded in the matrix cross-linking network through chemical reactions with epoxy resin, so that the dynamic bonds are not only evenly distributed but also form chemical bonds with the matrix, thus improving the mechanical properties and chemical stability of the overall material.
[0036] The introduction of dynamic bonds also gives the material a certain toughness at the molecular level, avoiding brittle failure caused by thermal cycling.
[0037] Micro-thermodynamics and diffusion inhibition: The presence of disulfide groups changes the motion pattern of the molecular segments of the matrix. Under high temperature conditions, the stress released by dynamic bond cleavage can reduce the local expansion of the matrix, reduce the dynamic opening of the diffusion path of water and oxygen molecules, and thus inhibit water and oxygen penetration.
[0038] Synergistic barrier effect: The combination of dynamic bonds and nanofillers further optimizes the microstructure of the encapsulation layer. The fillers prevent the direct diffusion of water and oxygen molecules, while the dynamic bonds repair cracks at the molecular level, avoiding new diffusion channels formed by microcracks, thereby improving the comprehensive barrier performance of the material.
[0039] Preferably, the molecular sieve filler is ZSM-5 molecular sieve or MIL-101 metal organic framework material, and the mass proportion of the molecular sieve filler is 5-15%; Molecular sieve filler type: ZSM-5 molecular sieve: It has a regular silicon-aluminum-oxygen skeleton and a pore structure with a pore size of about 0.5nm, which can selectively block the entry of small molecules (water and oxygen). It also has good thermal stability and chemical inertness, and is suitable for high-temperature working environments.
[0040] MIL-101 Metal-Organic Frameworks (MOFs): It has ultra-high porosity and large specific surface area (>3000m 2 / g), with a pore size range of 0.8 to 1.2 nm, which can effectively block the diffusion of water and oxygen molecules through size screening effect.
[0041] Compatibility of molecular sieve filler and matrix: The molecular sieve filler is combined with the matrix (polydimethylsiloxane) through surface functionalization treatment (silanization modification) to enhance the interfacial compatibility and avoid microcracks caused by agglomeration or uneven distribution of the molecular sieve in the matrix.
[0042] Ratio range: The molecular sieve filler preferably accounts for 5 to 15% by mass. When it is less than 5%, the barrier performance of the filler cannot be fully exerted; when it is more than 15%, the fluidity of the matrix decreases and the interface detachment problem is caused by excessive filler.
[0043] Screening of molecular sieve effect: Pore size selectivity: The micropore size (0.5-1.2 nm) of molecular sieve fillers (ZSM-5 and MIL-101) is close to the size of water molecules (~0.28 nm) and oxygen molecules (~0.346 nm), but much smaller than the size of macromolecular pollutants. The microporous framework forms a size screening effect on water and oxygen molecules, effectively blocking them in the diffusion path.
[0044] Thermodynamic adsorption: The high specific surface area of the molecular sieve filler enhances the physical adsorption of water and oxygen molecules, capturing them in the micropores through hydrogen bonds or van der Waals forces, and delaying their further diffusion.
[0045] Pore structure and diffusion path extension: Multi-channel diffusion barrier of ZSM-5 molecular sieve: The microporous structure of ZSM-5 molecular sieve requires water and oxygen molecules to pass through multiple interlaced channels, which significantly prolongs the diffusion path and reduces the overall permeability. The extension of the diffusion path is reflected by the following formula: L ep is the equivalent diffusion path length; D eff The effective diffusion coefficient (EffectiveDiffusionCoefficient) indicates the overall diffusion rate of the material after adding the molecular sieve filler. The molecular sieve makes the effective diffusion coefficient smaller than the initial diffusion coefficient by extending the diffusion path; D0 is the initial diffusion coefficient of the matrix (Intrinsic Diffusion Coefficient), which refers to the intrinsic diffusion rate of the matrix material when there is no molecular sieve filler, which mainly depends on the molecular structure and molecular gap of the matrix; t is the actual thickness of the material (Thickness of the Material Layer), which refers to the thickness of the entire molecular sieve composite barrier layer; When molecular sieve fillers are present, the molecular diffusion path will become longer due to the selective filtering and blocking effect of the filler pores, L ep It is usually 3 to 5 times or more of the actual thickness t.
[0046] Ultra-high porosity of MIL-1011: The three-dimensional pore network of MIL-101 further increases the residence time of water and oxygen molecules when diffusing in the matrix, and the capture of water and oxygen molecules by its pores significantly improves the diffusion barrier efficiency.
[0047] Synergistic effect of molecular sieve filler and matrix: Enhanced interface compatibility: The surface of the molecular sieve filler treated by silanization forms a strong interface bond with the PDMS matrix, avoiding the interfacial penetration of water and oxygen due to interfacial defects. In addition, the improved interfacial compatibility enables the filler to be evenly distributed in the matrix, thereby maximizing the barrier performance.
[0048] Enhancement of barrier effect by uniformity of filler dispersion: Ultrasonic dispersion treatment allows the molecular sieve filler to be evenly distributed in the matrix in the form of flakes or particles. The evenly distributed filler can block the diffusion channel to the greatest extent, preventing water and oxygen molecules from freely diffusing through the matrix.
[0049] Thermal stability and mechanical reinforcement: Thermal stability of ZSM-5 and MIL-101: ZSM-5 molecular sieve has excellent thermal stability (>500°C), and MIL-101, although a MOFs material, also has a high thermal decomposition temperature (>300°C). These characteristics ensure that the molecular sieve filler will not fail under chip working conditions, thereby ensuring the long-term barrier performance of the encapsulation layer.
[0050] Enhanced mechanical properties: The rigid skeleton of the molecular sieve filler enhances the overall mechanical properties of the PDMS matrix, especially in high temperature and high humidity environments, significantly improving the deformation resistance of the encapsulation layer.
[0051] Synergistic barrier of molecular sieve filler and nano-montmorillonite: The microporous structure of ZSM-5 or MIL-101 screens the size of water and oxygen molecules, while the flaky structure of nano-montmorillonite forms a laminated physical barrier. The combination of the two significantly enhances the barrier effect of the composite layer, forming a dual barrier mechanism of "selective filtration + physical blocking".
[0052] Preferably, the inorganic filler is nano-montmorillonite, accounting for 3 to 10% by weight; Nano-montmorillonite Types: Modified montmorillonite: The organic montmorillonite modified with cations (dodecyl ammonium salt modified montmorillonite) has better hydrophobicity and dispersibility, which enables it to be evenly distributed in the matrix, avoiding the performance degradation caused by filler agglomeration.
[0053] Packing shape and size: Nano-montmorillonite is mainly in the form of a flake structure, with a thickness of 1 to 5 nm and a lateral size of hundreds of nanometers to several micrometers. Its high aspect ratio and interlayer structure can significantly extend the diffusion path of water and oxygen molecules.
[0054] Ratio range: The preferred mass proportion of nano-montmorillonite is 3-10%. When it is less than 3%, the flaky structure has little effect on the diffusion path and the barrier performance is difficult to significantly improve; when it is higher than 10%, the viscosity of the matrix is too high due to excessive filler, affecting the coating performance.
[0055] Layering effect: The flaky structure of nano-montmorillonite is randomly distributed in the matrix, but the stacking effect between adjacent flaky layers forms an efficient physical barrier. When water and oxygen molecules pass through the encapsulation layer, they have to bypass these flaky fillers, which significantly prolongs the diffusion path (the diffusion path can be several times longer than the original), thereby reducing the overall diffusion rate.
[0056] L ep is the equivalent diffusion path length; L0 is the intrinsic thickness of the substrate; Δl i It provides an additional diffusion path for water and oxygen molecules when bypassing the flake filler.
[0057] Micro channel closure: Montmorillonite flakes can fill the micropores and molecular gaps in the matrix, effectively reducing the free diffusion path of water and oxygen molecules in the matrix.
[0058] Interface bonding mechanism between flake filler and matrix: Through cationic modification, organic functional groups (alkyl chains or amino groups) compatible with the matrix are introduced to the surface of montmorillonite, which improves its compatibility with the PDMS matrix. This chemical compatibility enhances the bonding force between the filler and the matrix, avoiding the adverse effects of interface detachment or filler aggregation on performance.
[0059] The modified montmorillonite can also form a strong interface effect with the molecular sieve filler (ZSM-5) through the surface functional groups, further improving the overall barrier performance of the composite layer.
[0060] Thermal expansion adaptation mechanism: The flaky structure of nano-montmorillonite plays a stress dispersion role in the matrix, which can buffer the expansion of the matrix caused by thermal cycling, thereby reducing the formation of microcracks and enhancing the mechanical stability of the encapsulation layer under high temperature and high humidity conditions.
[0061] Synergistic barrier effect of nano-montmorillonite and molecular sieve: Molecular sieve screening effect: Molecular sieve (ZSM-5) uses its microporous structure to selectively block the size of water and oxygen molecules, thereby delaying their diffusion.
[0062] Path extension effect of flaky montmorillonite: The montmorillonite flakes further extend the diffusion path of water and oxygen molecules after bypassing the microporous structure. The combination of the two achieves a double barrier to water and oxygen molecules.
[0063] Mechanical Reinforcement: The montmorillonite sheet structure has high rigidity and high aspect ratio. When incorporated into the PDMS matrix, it can significantly improve the tensile strength and bending resistance of the composite material. The surfactant modified by montmorillonite can also enhance the dispersion between the sheets and avoid the degradation of mechanical properties caused by filler aggregation.
[0064] Optical clarity maintained: Since the thickness of the montmorillonite layer is only 1 to 5 nm, which is much smaller than the wavelength of visible light (400 to 700 nm), its introduction has little effect on the optical transparency of the substrate while maintaining the good light transmittance of the encapsulation layer.
[0065] Preferably, the matrix of the rigid molecular chain barrier layer is polyimide or polyaryletherketone containing aromatic rings, accounting for 60-80% by weight; Base Material: Polyimide (PI): It is produced by the polycondensation of aromatic diamine and aromatic dianhydride, and has a high glass transition temperature (Tg>300℃), excellent heat resistance and chemical stability. The presence of aromatic ring structure gives it rigid molecular chain characteristics, allowing it to maintain low molecular chain segment mobility in high temperature and high humidity environments.
[0066] Polyaryletherketone (PEEK): It is composed of aromatic ether bonds and ketone groups. It has high crystallinity, high thermal stability and chemical inertness, and has high mechanical strength.
[0067] Inorganic fillers: Fluorinated quartz particles (10-20% by mass): provide additional barrier capacity and mechanical reinforcement effects, while not significantly reducing the transparency of the encapsulation layer due to its excellent optical properties.
[0068] Crosslinking agent: Trifunctional crosslinking agent (trimethylolpropane triacrylate, 1-5% by mass): forms a dense three-dimensional network structure through crosslinking reaction, further improving the high temperature resistance and chemical stability of the material.
[0069] Rigid chain segment characteristics of aromatic ring structure: Polyimide and polyaryletherketone molecular chains contain a large number of aromatic ring structures, and these rigid structures significantly limit the mobility of the molecular chain segments. The low mobility of the molecular chain reduces the dynamic opening of the diffusion path of water and oxygen molecules, thereby significantly reducing the permeation rate of water and oxygen.
[0070] Dense arrangement of molecular chains: Polyimide and polyaryletherketone containing aromatic rings have highly dense molecular chain structures, which reduce the molecular gaps inside the material, thereby further improving the barrier capacity to water and oxygen molecules.
[0071] Synergistic barrier of inorganic fillers: Fluorinated quartz particles are used as inorganic fillers and are evenly distributed in the matrix to form an additional physical barrier structure. The presence of the filler significantly prolongs the diffusion path of water and oxygen molecules in the encapsulation layer, thereby achieving the dual barrier effect of "rigid chain barrier + filler barrier".
[0072] The surface properties of fluorinated quartz further reduce the adsorption of moisture by the encapsulation layer, weakening the corrosion effect of high humidity environment on the material.
[0073] Chemical stability of the cross-linked network: The trifunctional crosslinking agent reacts with polyimide or polyaryletherketone to form a three-dimensional crosslinked network structure. This crosslinked network further enhances the molecular chain connectivity of the matrix, allowing the material to maintain structural stability in high temperature and high humidity environments without causing performance degradation due to thermal expansion or hygroscopic expansion.
[0074] Thermal stability in high temperature and high humidity environment: Both polyimide and polyaryletherketone have relatively high glass transition temperature and decomposition temperature (>300°C), and can maintain a stable form under high temperature conditions when the LED chip is working, thus avoiding thermal degradation of the material.
[0075] The low coefficient of thermal expansion of fluorinated quartz allows for good matching with the substrate, further reducing the risk of interlayer cracking due to thermal cycling.
[0076] Mechanical Reinforcement: The high strength and high rigidity of polyimide and polyaryletherketone give the material excellent tensile strength and bending resistance, which can effectively protect the molecular sieve composite barrier layer and the internal phosphor encapsulation layer from damage by external mechanical stress.
[0077] The introduction of fluorinated quartz particles further improves the material's compressive resistance and surface hardness, enabling the encapsulation layer to work stably for a long time in harsh environments.
[0078] Maintaining optical performance: Due to the optical transparency of the polyimide and polyaryletherketone matrices and the high light transmittance of the fluorinated quartz particles (visible light transmittance > 95%), the rigid molecular chain barrier layer can provide high barrier properties while maintaining good optical properties without causing significant attenuation of the light emitted by the chip.
[0079] The three-dimensional cross-linked network is a grid-like molecular structure based on chemical bonding and has the following characteristics: Chemical connection point (cross-linking point): The three active groups of the cross-linking agent are respectively connected with three different polyimide or polyaryletherketone molecular segments through chemical reactions to form cross-linking points.
[0080] Each cross-linking point is composed of a central molecular core of the cross-linking agent and three bonded matrix chain segments.
[0081] Schematic: R1-[TMPA]-R2,R3 R1, R2, and R3 are different matrix molecular chains; [TMPA] is the central molecular core of the cross-linking agent.
[0082] Molecular Grid Structure: The cross-linking points are connected through the main chain segments of polyimide or polyaryletherketone to form a molecular grid with regularity or randomness.
[0083] Regular cross-linking: the cross-linking points are evenly distributed, the cross-linking density is low but the performance is uniform; Random cross-linking: The cross-linking points are randomly distributed in space, the cross-linking density is higher, and the material is denser.
[0084] Molecular cross-linking density: The number of cross-linking points between molecular chains determines the cross-linking density, and the preferred density range is 5 to 20 mol / m 3 Too low a crosslink density will not significantly improve the mechanical properties of the material, while too high a crosslink density may reduce flexibility.
[0085] Dimensional stability: The three-dimensional cross-linked network locks the molecular chain segments in a fixed space, restricting the free movement of the chain segments and effectively improving the dimensional stability of the material in high temperature and high humidity environments.
[0086] Preferably, the inorganic filler is fluorinated quartz particles, and the mass proportion of the inorganic filler in the rigid molecular chain barrier layer is 10-20%; Characteristics of quartz fluoride particles: Chemical properties: Fluorinated Quartz (SiO2-F) is formed by replacing some of the hydroxyl groups on the silicon-oxygen bonds with fluorine atoms. Its surface is highly chemically inert and has low surface energy, giving the material excellent water and oxygen repellency.
[0087] Particle size range: The particle size of the microparticles is preferably controlled within the range of 100 nm to 500 nm to ensure that they can achieve high dispersibility without significantly affecting the optical transparency of the material.
[0088] Ratio range: The mass proportion of fluorinated quartz particles is preferably 10-20%. When it is less than 10%, the barrier effect and reinforcement performance are insufficient; when it is more than 20%, the fluidity of the matrix decreases due to excessive fillers, and the film-forming performance deteriorates.
[0089] Surface modification: The fluorinated quartz particles are modified with a silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) to improve their dispersibility and interface bonding strength in a polyimide or polyaryletherketone matrix.
[0090] Chemically inert and hydrophobic: After the surface of fluorinated quartz is replaced by fluorine, it has extremely low surface energy, which forms a strong repulsive effect on water molecules and oxygen molecules, reducing the probability of water and oxygen adsorption on the surface of the material, thereby significantly reducing the hygroscopicity and oxygen permeability of the material.
[0091] Interface enhancement mechanism: The surface of the modified fluorinated quartz particles contains active functional groups (epoxy or hydroxyl), which can chemically bond with the functional groups in the polyimide or polyaryletherketone matrix to form a strong interface bond. This strong interface bond avoids the aggregation of particles or the generation of interface voids, and further enhances the mechanical properties and barrier properties of the encapsulation layer.
[0092] Thermal stability and low thermal expansion: Thermal expansion coefficient matching: fluorinated quartz particles have an extremely low thermal expansion coefficient (~0.55×10 -6 / ℃), and the thermal expansion coefficient of the polyimide or polyaryletherketone matrix (~20×10 -6 Its introduction can effectively reduce the thermal expansion mismatch caused by thermal cycling, thereby avoiding cracking or delamination of the packaging layer.
[0093] Enhanced thermal stability: The high thermal decomposition temperature (>1000°C) of fluorinated quartz particles enables them to maintain structural stability under high temperature conditions without thermal degradation, ensuring the long-term high temperature resistance of the encapsulation layer.
[0094] Mechanical Reinforcement: The introduction of fluorinated quartz particles as rigid inorganic fillers significantly improves the tensile strength, bending resistance and surface hardness of the matrix.
[0095] The uniform distribution of particles in the matrix effectively prevents the formation and expansion of cracks and significantly enhances the impact resistance of the encapsulation layer.
[0096] Optical performance retention mechanism: The refractive index of the fluorinated quartz particles is close to that of the polyimide or polyaryletherketone matrix (about 1.5-1.6), so no significant light scattering effect is introduced, thereby maintaining high optical transparency of the encapsulation layer (visible light transmittance>90%).
[0097] Preferably, the dynamic self-repairing bottom package is prepared by the following steps: Material Mixing: Components and proportions: Dynamic chemical network epoxy resin matrix: 60-80wt%; Dynamic bond introducing agent (disulfide group precursor): 5-15wt%; Nanofiller (multi-walled carbon nanotubes): 3-10 wt%; Surfactant (γ-aminopropyltriethoxysilane): 0.5-2 wt%.
[0098] Mixing process: The dynamic chemical network epoxy resin matrix is mixed with the dynamic bond introducing agent, and high-speed shear stirring (2000-3000 rpm) is adopted for 30-60 minutes to ensure that the dynamic bond introducing agent is evenly distributed in the matrix.
[0099] Add nano fillers and surfactants, and continue stirring (1500-2500 rpm) for 20-40 minutes to fully mix the fillers and the matrix and achieve uniform dispersion.
[0100] Vacuum degassing: The mixed slurry is placed in a vacuum environment for degassing, with the vacuum degree controlled at -0.08 to -0.1 MPa for 15 to 30 minutes. This step is used to remove bubbles generated during the mixing process to avoid structural defects caused by residual bubbles after curing.
[0101] Coating: Use a dispensing machine to evenly apply the degassed slurry on the surface of the LED chip. The coating thickness is controlled at 20 to 50 μm to ensure that the encapsulation layer is fully covered and has uniform thickness.
[0102] Initial curing: The initial curing is carried out in an environment of 80 to 100°C for 30 to 60 minutes, so that the dynamic bonds initially form a chemical network and the initial cross-linking of the matrix is completed.
[0103] High temperature curing: The secondary high temperature curing is carried out at 150-170°C for 1-2 hours. This step ensures the complete reaction of the dynamic bond (disulfide bond) and the complete formation of the dynamic chemical network.
[0104] Preferably, the molecular sieve composite barrier layer is prepared by the following steps: Material Mixing: Components and proportions: Polydimethylsiloxane (PDMS, matrix): 70-90 wt%, providing flexibility and thermal stability; Molecular sieve filler (ZSM-5 molecular sieve or MIL-101 metal organic framework material): 5-15wt%, providing molecular sieve effect; Inorganic filler (nano-montmorillonite): 3-8wt%, enhancing barrier performance and mechanical stability.
[0105] Mixing process: Add the PDMS matrix and the molecular sieve filler into the mixer in proportion, stir at high speed (1500-2000 rpm) for 20-40 minutes for preliminary mixing; After adding the inorganic filler (nano-montmorillonite), stir again at high speed to ensure that the filler is evenly distributed.
[0106] Ultrasonic dispersion: Process parameters: The mixed slurry is placed in an ultrasonic dispersion device with a frequency controlled at 40 to 60 kHz and a processing time of 30 to 60 minutes. The purpose of ultrasonic dispersion is to break up the agglomeration of the molecular sieve and the inorganic filler, ensure the uniform distribution of the filler particles in the matrix, and avoid the adverse effects of local concentration areas on material properties.
[0107] Spin coating process: Steps: The uniformly dispersed slurry is coated on the surface of the dynamic self-repairing bottom package by a spin coating device; The spin coating speed is controlled at 2000-3000 rpm to form a thin film layer with a thickness of 10-30 μm; The coated film should have a uniform surface, free of bubbles and defects to ensure the integrity of the barrier properties.
[0108] Curing treatment: Curing treatment is carried out at 80-100°C for 8-12 hours; During the curing process, the PDMS matrix undergoes a cross-linking reaction, and at the same time, the molecular sieve and the inorganic filler are combined with the matrix through physical action or interface interaction to form a dense composite barrier layer.
[0109] Preferably, the rigid molecular chain barrier layer is prepared by the following steps: Material Mixing: Components and proportions: Polyimide matrix (PI): 60-80 wt%, providing rigid molecular chain characteristics and thermal stability; Inorganic filler (fluorinated quartz particles): 10-20wt%, to enhance barrier properties and mechanical strength; Crosslinking agent (trimethylolpropane triacrylate, TMPA): 1-5 wt%, to increase the crosslinking density.
[0110] Mixing process: The polyimide matrix is dissolved in a high boiling point solvent (N,N-dimethylformamide, DMF), and stirred (1000-1500 rpm) for 20-40 minutes to form a uniform solution.
[0111] Add fluorinated quartz particles and crosslinking agent, and continue stirring for 30 to 60 minutes to ensure that the filler is evenly dispersed and fully combined with the matrix.
[0112] Solvent evaporation method to prepare coating: The mixture is evenly coated on a flat substrate to form a preliminary coating by solvent evaporation method: The temperature is controlled at 50-80°C and the evaporation time is 1-3 hours to ensure that the solvent is completely volatilized to form a uniform film.
[0113] Spraying process: The uniform slurry obtained after evaporation of the solvent is coated on the surface of the molecular sieve composite barrier layer through a spraying device: Spraying pressure: 0.1~0.2MPa; Spraying distance: 10-20cm; Spray film thickness: 10-15μm, ensuring the coating surface is uniform and free of defects.
[0114] Curing treatment: Curing treatment is carried out at 200-250°C for 20-40 minutes: High-temperature curing completes the cross-linking reaction of the polyimide molecular chains and firmly embeds the inorganic fillers into the matrix to form a dense three-dimensional cross-linked network structure.
[0115] The present invention provides a packaging method for improving the reliability of cyan phosphors. It has the following beneficial effects: 1. The present invention adopts dynamic self-repairing bottom packaging technology, and significantly improves the crack healing ability and mechanical stability of the packaging material by introducing a dynamic chemical network and a high cross-linking density epoxy resin matrix. Compared with the technical solution in the prior art where a single high cross-linking epoxy resin network is prone to irreversible damage, the present invention effectively solves the problem of packaging failure caused by crack expansion and prolongs the service life of the packaging layer.
[0116] 2. The present invention significantly reduces the water and oxygen permeability through the design of the molecular sieve composite barrier layer, combined with the microporous screening effect of the molecular sieve filler and the laminated barrier effect of the inorganic filler. Compared with the barrier solution relying on a single flexible substrate in the prior art, the present invention solves the problem of short diffusion path and high permeability of the traditional barrier layer, and provides a more reliable water and oxygen barrier for packaging.
[0117] 3. The present invention innovatively uses a rigid molecular chain matrix containing aromatic rings, supplemented by fluorinated quartz fillers and crosslinking agents, to construct a barrier layer with high density and high mechanical strength. Compared with the prior art solution in which flexible polymer coatings are prone to deformation or cracking under high temperature environments, the present invention significantly improves the dimensional stability and high temperature resistance of the encapsulation layer, ensuring the reliability of the encapsulation under long-term working conditions under harsh conditions.
[0118] 4. The present invention adopts a multi-layer structure step-by-step preparation process, and optimizes the uniformity and interface bonding of the film through solvent evaporation, spraying and high-temperature curing. The problem of thin film layer delamination or cracking due to insufficient interface bonding in the prior art is effectively solved. The present invention maintains optical transparency while achieving high barrier performance, providing a guarantee for the light color stability of phosphor encapsulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0119] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0120] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0121] Example 1: Preparation of dynamic self-repairing bottom package: Take 60% of bisphenol A epoxy resin (EPON828) by weight as the matrix, add 10% of disulfide group precursor (2,2'-dithiodibenzoic acid), and then mix with a high-speed shear mixer, set the speed to 2500rpm, and the time is 45 minutes. Subsequently, add 5% of multi-walled carbon nanotubes and 1% of silane coupling agent (γ-aminopropyltriethoxysilane) and stir again for 30 minutes. The whole process ensures that the mixture has no obvious agglomeration.
[0122] The mixed slurry is placed in a vacuum environment for degassing. The vacuum degree is controlled at -0.1MPa and the degassing time is 20 minutes to ensure that bubbles are removed.
[0123] Use a dispensing machine to evenly coat the mixed slurry on the surface of the LED chip with a coating thickness of 30μm. Keep the coating smooth and free of defects.
[0124] The initial curing temperature was set at 90°C for 40 minutes. The temperature was then raised to 160°C for high-temperature curing for 1.5 hours. The surface of the cured encapsulation layer was smooth and dense, with no bubbles or cracks.
[0125] Example 2: Preparation of molecular sieve composite barrier layer: Weigh 80% of polydimethylsiloxane (PDMS) matrix according to proportion, add 10% of ZSM-5 molecular sieve (particle size 400nm) and 5% of nano-montmorillonite, and stir with a magnetic stirrer at 1800rpm for 30 minutes to ensure preliminary uniform mixing.
[0126] The mixed slurry was placed in an ultrasonic disperser with the frequency set to 50 kHz and the treatment time set to 40 minutes. After observing the slurry, it was ensured that the molecular sieve and montmorillonite particles were evenly dispersed in the matrix without obvious agglomeration.
[0127] The mixed slurry was coated using a spin coating process, the spin coating speed was set to 2500 rpm, and the coating thickness was controlled at 20 μm. The surface of the coated film was uniform and the thickness was consistent.
[0128] The film was cured at 80°C for 10 hours to form a highly dense composite barrier layer without pores or defects.
[0129] Example 3: Preparation of Rigid Molecular Chain Barrier Layer: Weigh 70% of polyimide and dissolve it in N,N-dimethylformamide (DMF) with a stirring speed of 1000 rpm for 30 minutes. After it is completely dissolved, add 15% of fluorinated quartz particles (particle size 300nm) and stir for 40 minutes. Then add 3% of trimethylolpropane triacrylate (TMPA) crosslinking agent and stir again for 30 minutes.
[0130] The mixed slurry was evenly coated on the surface of the flat substrate to form a coating by solvent evaporation. The temperature was set to 60°C and the time was 2 hours to ensure that the solvent was completely volatilized and a preliminary film was formed.
[0131] The slurry was coated on the surface of the molecular sieve composite barrier layer by spraying process, the spraying pressure was set to 0.15 MPa, the spraying distance was 15 cm, and the coating thickness was controlled at 15 μm.
[0132] The film was cured at 230°C for 30 minutes to ensure complete cross-linking reaction. After curing, a dense three-dimensional cross-linked network structure was formed without obvious cracking or delamination.
[0133] Example 4: Preparation of multi-layer packaging: First, a dynamic self-repairing bottom package is prepared (refer to Example 1). After curing, the bottom package has a smooth surface and has self-repairing capability.
[0134] The molecular sieve composite barrier layer is coated on the surface of the dynamic bottom package (refer to Example 2). After the spin coating is completed, the film surface is uniform and has no defects, and is cured to form a flexible barrier layer.
[0135] Finally, a rigid molecular chain barrier layer is sprayed on the surface of the molecular sieve composite barrier layer (see Example 3). After the spraying is completed, it is cured to obtain the final multi-layer packaging structure.
[0136] Example 5: Overall performance test: A complete multi-layer packaging structure was prepared, using a dynamic self-repairing bottom layer, a molecular sieve composite barrier layer and a rigid molecular chain barrier layer (refer to Examples 1 to 3).
[0137] Comparative Example 1: Comparison of dynamic self-repairing bottom package: Comparison of process flow: 80% of bisphenol A epoxy resin is taken as the matrix material by weight, no dynamic bond introducing agent is introduced, and only 10% of multi-walled carbon nanotubes are added as filler.
[0138] Use a high-speed stirrer with the speed set to 2000 rpm. Stir for 30 minutes and then perform vacuum degassing with a vacuum degree of -0.08 MPa for 15 minutes.
[0139] The coating thickness was controlled at 25 μm, and then the coating was directly cured at 90° C. for 1 hour.
[0140] The cured coating was not subjected to secondary high-temperature curing and was directly tested as an encapsulation layer.
[0141] Comparative Example 2: Comparison of molecular sieve composite barrier layer: Comparison of process flow: The polydimethylsiloxane (PDMS) matrix was taken at a ratio of 90 wt%, and 5 wt% of ZSM-5 molecular sieve was added as filler, and no nano-montmorillonite was added.
[0142] The mixed material was directly coated after being stirred with a magnetic stirrer for 20 minutes without using an ultrasonic dispersion process.
[0143] The coating was carried out using a spin coating process, the spin coating speed was set to 2000 rpm, and the film thickness was controlled at 15 μm.
[0144] The coated film was cured at 60°C for 6 hours.
[0145] Comparative Example 3: Comparison of Rigid Molecular Chain Barrier Layer: Comparison of process flow: The polyimide matrix was dissolved in N,N-dimethylformamide (DMF) at a ratio of 65 wt %, and 15 wt % of fluorinated quartz particles were added, and the stirring time was 20 minutes.
[0146] Without adding a trifunctional crosslinking agent, the coating was directly prepared by solvent evaporation at a temperature of 50° C. for 1 hour.
[0147] The coating was applied by manual scraping process with a film thickness of 20 μm.
[0148] The curing temperature was set at 180°C and the curing time was 30 minutes.
[0149] Comparative Example 4: Combination comparison of dynamic self-repairing bottom layer and molecular sieve composite barrier layer: Comparison of process flow: The dynamic self-repairing bottom layer was prepared according to Comparative Example 1 without using a dynamic bond introducing agent.
[0150] The molecular sieve composite barrier layer was prepared according to Comparative Example 2, without adding nano-montmorillonite and without using ultrasonic dispersion process.
[0151] Comparative Example 5: Comparison of multi-layer packaging structures: Comparison of process flow: The dynamic self-repairing bottom layer is prepared according to Example 1; The molecular sieve composite barrier layer was prepared according to Comparative Example 2, without using the ultrasonic dispersion process; The rigid molecular chain barrier layer was prepared according to Comparative Example 3, without adding a crosslinking agent, and the curing temperature was set to 180°C.
[0152] Comparative Example 6: Comparison of single-layer packaging: Comparison of process flow: A single-layer packaging structure is adopted, and only the dynamic self-repairing bottom layer in Example 1 is used as the packaging layer.
[0153] The thickness of the dynamic self-healing layer is increased to 100 μm, which is applied and cured by a dispensing process.
[0154] No molecular sieve composite barrier layer and rigid molecular chain barrier layer are added.
[0155] Experiment 1: Water Vapor Transmission Rate (WVTR) Test: Sample preparation: Example samples: Prepare samples of Example 2 (molecular sieve composite barrier layer) and Example 5 (multilayer packaging structure), ensure the surface is uniform, and the thickness is 20 μm and 50 μm respectively.
[0156] Comparative example samples: Comparative example 2 (molecular sieve composite barrier layer is not ultrasonically dispersed) and comparative example 5 (multilayer packaging structure, molecular sieve composite barrier layer is not ultrasonically dispersed and rigid molecular chain barrier layer is not cross-linked) were prepared, and the sample thickness was consistent with that in the embodiment.
[0157] Experimental conditions: The water vapor transmission rate tester (Mocon PERMATRAN) was used according to ASTM F1249 standard.
[0158] The test environment was set at 85°C / 85%RH, and a constant humidity and temperature chamber was used to ensure stable humidity and temperature.
[0159] Each sample was tested 3 times and its water vapor transmission rate (unit: g / m 2 ·day).
[0160] Test steps: Secure the sample in the tester's clamps, ensuring a good seal and avoiding leakage around the edges.
[0161] Start the tester, monitor the water vapor transmission on both sides of the sample in real time through the humidity sensor, and record the steady-state transmission rate data.
[0162] After each test, the samples were taken out and checked for any cracks or local failures.
[0163] Repeat the above operation and record the average value of the three tests. The experimental data of the water vapor transmission rate (WVTR) test results of different samples are shown in the following table: in conclusion: The water and oxygen barrier performance of Examples 2 and 5 is significantly better than that of the comparative example, showing a lower water vapor permeability. This is due to the microporous screening effect and dispersion uniformity of the molecular sieve composite barrier layer, as well as the synergistic effect of the multi-layer packaging structure. The dynamic repair layer and the rigid molecular chain barrier layer further reduce the possibility of water and oxygen penetration.
[0164] In the comparative example, due to the lack of ultrasonic dispersion and cross-linking curing treatment, the molecular sieve filler agglomerates and the interface bonding force is poor, which significantly reduces the barrier performance. The test results fully demonstrate the superiority of the multi-layer design and optimized process of the present invention in improving the water and oxygen barrier performance.
[0165] Experiment 2: High temperature and high humidity aging test: Sample preparation: Prepare the following samples: Example 4: A multilayer structure using a dynamic self-healing bottom layer encapsulation, a molecular sieve composite barrier layer and a rigid molecular chain barrier layer.
[0166] Comparative Example 1: The dynamic self-repairing bottom layer does not introduce dynamic bonds and is only a highly cross-linked epoxy resin.
[0167] Comparative Example 4: A dynamic bottom layer and a molecular sieve composite barrier layer are combined without a rigid barrier layer.
[0168] The package thickness of each sample was controlled at 50 μm.
[0169] Experimental conditions: Placed in a high temperature and high humidity aging box, the experimental conditions were set to 85°C / 85%RH and the duration was 1000 hours.
[0170] Every 200 hours, samples are taken to test the light output intensity and record the light decay.
[0171] Test steps: Fix the samples in the aging box to ensure stable environmental parameters.
[0172] During each test, the sample is removed from the aging box, and its light output intensity is measured using a photometer, and the decrease ratio (light decay rate) relative to the initial value is recorded.
[0173] Check the appearance of the sample to see if there are any failure phenomena such as delamination, cracks or discoloration.
[0174] Repeat the above operation until the end of the experiment. The experimental data of the light decay rate comparison results during the high temperature and high humidity aging process are shown in the following table: in conclusion: The multilayer package of Example 4 exhibits excellent light decay stability under high temperature and high humidity conditions. The dynamic chemical network effectively repairs the cracks generated during the aging process, the molecular sieve barrier layer prevents water and oxygen from penetrating, and the rigid molecular chain provides additional protection. The light decay rate is always maintained at a low level.
[0175] The comparative samples lacked dynamic repair ability and mechanical strength, so cracks expanded rapidly, barrier properties decreased, and light decay accelerated. This result verifies the reliability and superiority of the multi-layer structure in harsh environments.
[0176] Experiment 3: Dynamic repair capability test: Sample preparation: Example 1: Preparation of a dynamic self-healing bottom layer package containing a dynamic chemical network with a thickness of 30 μm.
[0177] Comparative Example 1: A highly cross-linked epoxy resin encapsulation layer without a dynamic bond introducing agent was prepared, with a thickness of 30 μm.
[0178] The sample was cut into a standard dumbbell shape with a width of 5 mm and a length of 50 mm.
[0179] Experimental equipment and conditions: An electronic tensile testing machine was used with a tensile speed of 10 mm / min.
[0180] The sample was initially stretched until the stress reached its maximum value, resulting in obvious cracks but no breakage.
[0181] The sample was placed in a 120°C constant temperature box and left to stand for 30 minutes to trigger the self-repair behavior of the dynamic chemical network.
[0182] After repair, re-perform the tensile test and record the breaking stress value.
[0183] Experimental steps: The sample was fixed in the clamp of the tensile testing machine, stretched until cracks appeared and the maximum stress (initial fracture stress) was recorded.
[0184] The cracked sample was moved into a thermostatic box, maintained at 120°C for 30 minutes, and then taken out.
[0185] Fix it on the tensile testing machine again, repeat the tensile test and record the fracture stress after repair.
[0186] Repeat the above operation 3 times and calculate the average value. The dynamic repair ability test results (fracture stress recovery rate) experimental data are shown in the following table: in conclusion: The dynamic chemical network exhibited efficient self-repairing ability in Example 1, with a fracture stress repair rate of over 85%. The disulfide bonds were broken, absorbed energy and reorganized, and the material properties were restored, showing a strong crack repair function.
[0187] Due to the lack of dynamic key design, the cracks in the comparative samples were out of control and the fracture stress recovery rate was less than 50%. The experiment clearly demonstrated the key role of dynamic repair technology in improving the life and stability of materials.
[0188] Experiment 4: High temperature mechanical properties test: Sample preparation: Example 3: A rigid molecular chain barrier layer containing a polyimide matrix, fluorinated quartz particles and a trifunctional crosslinking agent is used, with a thickness of 15 μm.
[0189] Comparative Example 3: A rigid molecular chain barrier layer without adding a crosslinking agent and having a curing temperature of 180° C. was prepared, with a thickness of 15 μm.
[0190] The samples were cut into a standard dumbbell shape with a width of 5 mm and a length of 50 mm.
[0191] Experimental equipment and conditions: The tensile strength was tested using an electronic tensile testing machine in accordance with ASTM D638.
[0192] The tests were carried out at room temperature (25°C) and high temperature (150°C) respectively, and the tensile strength of the samples was recorded.
[0193] The tensile speed was set to 10 mm / min to ensure a stable test process.
[0194] Test steps: Fix the sample in the clamp of the tensile testing machine to ensure that the sample is evenly stressed.
[0195] The specimens were stretched to break at room temperature and the breaking strength was recorded.
[0196] In the high temperature test, the sample was preheated to 150°C, maintained at this temperature for 10 minutes, and then the tensile test was started and the breaking strength was recorded.
[0197] Each sample was tested 3 times and the average value was taken. The tensile strength test data of different samples at room temperature and high temperature are shown in the following table: in conclusion: Example 3 can still maintain a high tensile strength at high temperature, thanks to the synergistic reinforcement of the three-dimensional cross-linked network and fluorinated quartz. The material structure is stable, the molecular chain movement is restricted, and the mechanical property loss is small.
[0198] In comparative example 3, due to lack of crosslinking agent support, the molecular chain slides at high temperature and the tensile strength is significantly reduced. This verifies the superior performance of the rigid molecular chain barrier layer of the present invention in a high temperature environment.
[0199] Experiment 5: Layered bonding test: Sample preparation: Example 5: A multilayer packaging structure comprising a dynamic self-repairing bottom layer packaging, a molecular sieve composite barrier layer, and a rigid molecular chain barrier layer was prepared, with thicknesses of 30 μm, 20 μm, and 15 μm, respectively.
[0200] Comparative Example 5: A multi-layer packaging structure was prepared without using the ultrasonic dispersion process and without cross-linking the rigid molecular chain barrier layer, and the thickness setting was the same as that of Example 5.
[0201] The samples were cut into strips with a width of 10 mm and a length of 50 mm.
[0202] Experimental equipment and conditions: The peeling force between the layers of the sample was tested using a tensile peel tester according to ASTM D1876.
[0203] The temperature is divided into two groups of tests: room temperature (25°C) and high temperature (85°C), simulating the bonding performance under conventional and harsh environments.
[0204] Experimental steps: One end of the sample was fixed in a fixture and the peeling angle was set to 90°.
[0205] The peeling test was started, and the film was stretched gradually at a speed of 10 mm / min, and the maximum peeling force (in N) of each layer during the peeling process was recorded.
[0206] The peeling forces between the bottom layer and the molecular sieve layer, and between the molecular sieve layer and the rigid layer were tested respectively.
[0207] The test was repeated 3 times under each condition and the average value was taken. The experimental data of the layered bonding strength of the multi-layer packaging structure measured are shown in the following table: in conclusion: The interlayer bonding force of the multilayer encapsulation of Example 5 is still stable at high temperature, and the dynamic bottom layer, molecular sieve layer and rigid molecular chain layer are tightly bonded. The dynamic repair bottom layer and the cross-linked network provide excellent interface adhesion performance.
[0208] Due to the lack of ultrasonic dispersion and cross-linking curing, the delamination phenomenon in Comparative Example 5 is serious and the peeling force is significantly reduced. The experiment shows that the multi-layer design of the present invention has more advantages in terms of interlayer bonding strength and thermal stability.
[0209] Experiment 6: Optical transmittance test: Sample preparation: Example 5: A multilayer packaging structure of a dynamic self-repairing bottom layer, a molecular sieve composite barrier layer, and a rigid molecular chain barrier layer was prepared, with a final thickness of 50 μm.
[0210] Comparative Example 6: Prepare a single-layer dynamic self-repairing bottom packaging structure with a thickness of 50 μm.
[0211] Experimental equipment and conditions: The optical transmittance of the samples in the visible light range (400–700 nm) was tested using a spectrophotometer according to ASTM D1003.
[0212] The sample size was cut to 20 mm × 20 mm, and the test environment temperature was 25 °C.
[0213] The test light source is a white light source, and the beam diameter is set to 5 mm.
[0214] Experimental steps: Fix the sample in the sample holder of the spectrophotometer, making sure that the light beam completely passes through the center area of the sample.
[0215] Measure the transmittance of the sample every 10nm in the wavelength range of 400-700nm and record the spectral curve.
[0216] Each sample was tested 3 times and the average value was taken.
[0217] By comparing the light transmittance of the multi-layer structure with that of the single-layer structure and evaluating the influence of the multi-layer design on the optical performance, the optical transmittance experimental data of the samples in the visible light band are shown in the following table: in conclusion: The transmittance of the multi-layer packaging structure of Example 5 in the visible light band is slightly lower than that of Comparative Example 6, but is always maintained above 90%. The transparency design of the molecular sieve filler and the rigid molecular chain layer effectively avoids the light scattering problem.
[0218] Although the transmittance of comparative example 6 is slightly higher, it lacks mechanical and barrier properties and is difficult to meet the needs of practical applications. The multilayer structure achieves a better balance between optical performance and protection ability.
[0219] Experiment 7: Thermal Cycle Stability Test: Sample preparation: Example 5: A multi-layer packaging structure consisting of a dynamic self-repairing bottom layer, a molecular sieve composite barrier layer, and a rigid molecular chain barrier layer, with a total thickness of 50 μm.
[0220] Comparative Example 5: A multilayer packaging structure of a molecular sieve composite layer without ultrasonic dispersion and a rigid molecular chain barrier layer without cross-linking, the thickness of which is consistent with that of Example 5.
[0221] Each sample was cut into a 50 mm × 50 mm square sheet, ensuring that the edges were flat and free of cracks.
[0222] Experimental equipment and conditions: Thermal cycle tester, the temperature range is set from -40℃ to 85℃.
[0223] The heating and cooling rate was set at 5°C / min, and the high and low temperature conditions were maintained for 30 minutes each cycle.
[0224] The total number of test cycles is 500 times, and the packaging layer is observed for failure phenomena such as cracks, delamination, and peeling.
[0225] Experimental steps: The sample is fixed in the test machine fixture to ensure uniform temperature conduction.
[0226] Set the cycle conditions, start the thermal cycle test, and record the changes in the sample's appearance after every 100 cycles.
[0227] After the test, the surface and interlayer state of the samples were checked with a microscope, and the number of cracks and the range of delamination were recorded. The failure data of the samples in the thermal cycle test were shown in the following table: in conclusion: After 500 thermal cycles, only slight cracks appeared in Example 5, and the delamination surface was extremely small, showing excellent thermal stability. The dynamic bottom layer relieved the interfacial stress, the rigid molecular chain layer improved the overall strength, and the molecular sieve layer maintained its compactness.
[0228] In Comparative Example 5, cracks and delaminations spread rapidly due to insufficient interface bonding and unstable rigid layer. The experimental results clearly demonstrate the adaptability and crack resistance of the multilayer design of the present invention to complex thermal cycle conditions.
[0229] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A packaging method for improving the reliability of cyan phosphor, characterized in that: The following steps are involved: S1. forming a dynamic self-repairing bottom package on the surface of the chip, wherein the dynamic self-repairing bottom package comprises a dynamic chemical network epoxy resin matrix, a dynamic bond introducing agent, a nanofiller and a surfactant; S2. coating a molecular sieve composite barrier layer on the dynamic self-repairing bottom package, wherein the molecular sieve composite barrier layer comprises a polydimethylsiloxane matrix, a molecular sieve filler, an inorganic filler and a toughening agent; S3, spraying a rigid molecular chain barrier layer on the molecular sieve composite barrier layer, wherein the rigid molecular chain barrier layer comprises a polyimide matrix, an inorganic filler and a cross-linking agent; S4, solidifying each layer in turn, and performing heat treatment on the entire package after completion.
2. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The dynamic chemical network epoxy resin matrix is bisphenol A epoxy resin or epoxy resin containing imide bonds, with a mass proportion of 60 to 80%.
3. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The dynamic bond introducing agent is a disulfide group precursor, with a mass proportion of 5 to 15%.
4. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The molecular sieve filler is ZSM-5 molecular sieve or MIL-101 metal organic framework material, and the mass proportion of the molecular sieve filler is 5-15%.
5. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The inorganic filler is nano-montmorillonite, which accounts for 3-10% by weight.
6. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The matrix of the rigid molecular chain barrier layer is polyimide or polyaryletherketone containing aromatic rings, with a mass proportion of 60 to 80%.
7. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The inorganic filler is fluorinated quartz particles, and the mass proportion of the inorganic filler in the rigid molecular chain barrier layer is 10-20%.
8. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The dynamic self-repairing bottom package is prepared by the following steps: mixing a dynamic chemical network epoxy resin matrix, a dynamic bond introducing agent, a nanofiller, and a surfactant; It is processed by high-speed stirring and coated after vacuum degassing; Initially cure at 80-100°C and cure at 150-170°C for 1-2 hours.
9. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The molecular sieve composite barrier layer is prepared by the following steps: Mixing polydimethylsiloxane, molecular sieve filler and inorganic filler, and performing ultrasonic dispersion; The thin film layer is formed by coating using a spin coating process; Curing at 80-100°C for 8-12 hours.
10. The packaging method for improving the reliability of cyan phosphor according to claim 1, characterized in that: The rigid molecular chain barrier layer is prepared by the following steps: The polyimide matrix, the inorganic filler and the cross-linking agent are mixed, and the coating is prepared by a solvent evaporation method; Forming a thin film by a spraying process; Curing at 200-250°C for 20-40 minutes.